2017
DOI: 10.1186/s12889-017-4273-0
|View full text |Cite
|
Sign up to set email alerts
|

Findings from a prospective cohort study evaluating the effects of International Health Advisors’ work on recently settled migrants’ health

Abstract: BackgroundSeveral interventions have been carried out to tackle health inequalities between migrant groups, especially refugees, and native-born European populations. These initiatives are often address language or cultural barriers. One of them is the International Health Advisors (IHA) in Sweden; a peer education intervention aimed at providing health information for recently settled migrants. It is known that social determinants, such as educational level and access to social capital, affect health. Social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 46 publications
3
19
0
Order By: Relevance
“…The results are notable as they indicate that about 40% of the refugees are at increased risk of further health problems, as self-perceived health is associated with sick leave (Carneiro et al 2013 ), mortality, and morbidity (Chandola and Jenkinson 2000 ). The high proportion of refugees having reported that they have refrained from seeking healthcare is consistent with, as far as we know, the only previous study examining this among refugees (Lecerof et al 2017 ). However, as our study included refugees from other countries of origin than the previous study, the results imply validity for other groups of refugees as well.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The results are notable as they indicate that about 40% of the refugees are at increased risk of further health problems, as self-perceived health is associated with sick leave (Carneiro et al 2013 ), mortality, and morbidity (Chandola and Jenkinson 2000 ). The high proportion of refugees having reported that they have refrained from seeking healthcare is consistent with, as far as we know, the only previous study examining this among refugees (Lecerof et al 2017 ). However, as our study included refugees from other countries of origin than the previous study, the results imply validity for other groups of refugees as well.…”
Section: Discussionsupporting
confidence: 89%
“…Another limitation in the use of self-reporting measurements in the study is that views on health and healthcare can vary with the country of birth and its culture (Ingleby 2012 ; Suphanchaimat et al 2015 ) and thus could influence interpretations of and answers to health-related questions. However, the measures used for self-reported general health, psychological well-being, and long-term illness are all three established instruments and indicators used in research and public health surveys in many different countries and cultures (Eurostat Statistics Explained 2016 ; Goldberg et al 1997 ; Lecerof et al 2017 ; Nielsen and Krasnik 2010 ; Sorensen et al 2015 ). Different views of health and health-seeking behaviors could also have affected the interpretations of and answers to the question about having refrained from seeking healthcare.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations